(untitled) (American Journal of Technology and Applied Sciences, 2026)
This paper compared the adoption of emerging technologies for workplace safety in manufacturing industries across Nigeria, China and USA. Six emerging technologies were explored. Technological, and Organizational factors were used to express adoption determinant factors. Cross-sectional research design was adopted. Stratified random sampling technique was used. Sample sizes were 449, 440 and 345 for USA, China, and Nigeria respectively determined using Taro Yamane’s sample size determination formula. Data were collected using checklist and structured questionnaire based on 2-point and 5-point Likert scale respectively. SPSS version 24 was used for data analyses; percentages and weighted mean scores (WMS) were computed using descriptive statistics. Results revealed that availability of emerging technology was high in China (84.86%) and USA (87.86%) and low in Nigeria ((24.64%), emerging technology adoption was high in USA (WMS=4.46>3.00) and China (WMS=4.26>3.00) and low in Nigeria (WMS=2.94<3.00). The determinant factors were predominant in China (WMS=4.32 and 4.24 >3.00) and USA (WMS=4.53 and 4.57>3.00) but moderate in Nigeria (WMS=3.13 and 3.21 > 3.00). it was concluded that, emerging technology adoption is dominate and high in developed countries like USA and China due to improved technological and organizational infrastructures and readiness and low in developing countries due to lack of technological and organizational infrastructures. Hence. stakeholders in manufacturing sector in developing countries like Nigeria should provide infrastructure and regulatory framework required to meetup with the required standard and level of emerging technology for workplace safety in the manufacturing sector.